Covid-19 Through the Lens of the Peer-Reviewed Literature. Issue 4 (29th July 2020) - Neal, Samuel R.; Zheng, Cindy
Abstract: What can we learn about the coronavirus pandemic from text-mining the titles of journal papers? By Samuel R. Neal and Cindy Zheng